Peranan Manajemen Seni Teater dalam Menanamkan Nilai-Nilai Akhlak Mulia - Sumantri Sumantri (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
This study aims to describe the role of extracurricular management in instilling noble moral values in the theater group Diah Mekar Harum, the role of theater arts extracurricular management and supporting factors and inhibiting the activities of implementing theater art extracurricular management in instilling noble moral values. Data collection techniques that is used are observation, documentation and interviews. The data collected is then processed through three stages namely data reduction, data display, and data verification, thenconclusions are drawn and qualitatively analyzed. The steps used in instilling the values of noble morals are through habituation, example, awareness and supervision. The results of the analysis show that the role of the management of the art of extracurricular theater in instilling moral values in the theater group Diah Mekar Harum which includes religious values, discipline, responsibility, creative, have independence, cooperation and care for the environment. The implications of this research are: 1) carrying out routine training activities that are conditioned leading to the cultivation of noble moral values that have been developed, 2) the roles and efforts that have been made by extracurricular theater arts builders need innovation by utilizing the potential of available educational resources for ongoing guidance, 3) parental support in the form of active participation in every theater arts extracurricular activity at SMK Negeri 1 Kayuagung.